SINDHI-MADRASAH AND TEACHINGS OF MAKHDOOM MOEEN - Muhammad Anas Rajpur; Zain ul Abdin (دی اسکالر)
Makhdoom Muhammad Mu’een Thatvi is regarded by the historian as one of the prominent and profound Islamic scholar of twelfth Century AH. His life and works have been adequately studied and examined by the learned scholars. This paper specifically studies in to his main contribution towards disseminating Islamic education in this region.  In order to achieve this noble cause, he established a high level religious seminary having boarding and lodging facility, where he dedicated all his life to teaching and mentoring scholars. Despite the scarcity of financial resources, he through this academic activity he was successful in preparing great scholars of the day and produced considerable number of books in the field.